KAMPANIA PROPAGANDOWA W SPRAWIE ORĘDZIA BISKUPÓW POLSKICH DO BISKUPÓW NIEMIECKICH Z 1965 ROKU W ŚWIETLE PRASY Z WROCŁAWIA I ZIELONEJ GÓRY - Sławomir Krzyżanowski (In Gremium. Studies in History, Culture and Politics, 2010)
PROPAGANDA CAMPAIGN ON THE LETTER OF RECONCILIATION OF THE POLISH BISHOPS TO THE GERMAN BISHOPS AS OF 1965 IN THE LIGHT OF WROCŁAW 'S AND ZIELONA GÓRA'S NEWS MEDIA The article is devoted to a significant event, namely the creation of the memorable Letter of Reconciliation of the Polish Bishops to the German Bishops as of 18 November 1965. "This fact undoubtedly contributed to the breach of the deadlock in the Polish German relationship following the Second World War.Simultaneously, it aroused controversy within the PZPR (Polish United Workers' Party) and became another reason to attack Polish Catholic Church. The basic tool to fight the Church ar the disposal of the authorities, was press propaganda used as a mca ns 10 reach the consciences of numerous Poles. The aim of the article is to analyse the above mentioned issues in the light of news media in the western areas of Poland; more precisely the Wrocław's press- including 'Gazeta Robotnicza' and 'Słowo Polskie' and the Zielona Góra's press- 'Gazeta Zielonogórska'. The above mentioned newspapers' names constituted the press body of the Voivodship Commirrces of the PZPR.These newspapers tried to cover the course of the entire propaganda campaign from the very beginning on the 13'11 of December 1965 when the first articles in 'Słowo Polskie' appeared, until the moment the campaign started to fade out and was granted a new dimension by the communists. 1l1e new dimension was connected with the Polish millennium.